2012
DOI: 10.1016/j.jtcvs.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-term mortality and cardiac transplantation in infants with single-ventricle lesions: Risk factors and their interaction with shunt type

Abstract: Objectives We sought to identify factors associated with death and cardiac transplantation in infants undergoing the Norwood procedure and to determine differences in associations that might favor either the modified Blalock-Taussig shunt (MBTS) or a right ventricle-to-pulmonary artery shunt (RVPAS). Methods We used competing risks methodology to analyze death without transplantation, cardiac transplantation, and survival without transplantation. Parametric time-to-event modeling and bootstrapping were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 26 publications
5
101
1
1
Order By: Relevance
“…Tweddell et al evaluated the role of neighborhood SES as one of the preoperative risk factors for 1‐year death and found that lower SES was associated with higher early mortality within the first year but not late phase mortality over 3 years 5. In contrast, Ghanayem et al used a census‐based neighborhood poverty level and found an inverted U‐shaped relationship between poverty level and interstage mortality 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tweddell et al evaluated the role of neighborhood SES as one of the preoperative risk factors for 1‐year death and found that lower SES was associated with higher early mortality within the first year but not late phase mortality over 3 years 5. In contrast, Ghanayem et al used a census‐based neighborhood poverty level and found an inverted U‐shaped relationship between poverty level and interstage mortality 8.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, risk factors for adverse outcome in the SV population have been the subject of many investigations. Among these, innate risk factors, such as low birth weight, anatomy, preterm birth, genetic abnormalities, and associated noncardiac congenital anomalies, are well‐established predictors for early mortality and transplantation 3, 4, 5, 6, 7, 8. Recently, societal factors such as poverty, medical insurance, and maternal education have emerged as predictors of adverse outcomes in children with complex congenital heart disease (CHD) and may explain some of the difference in survival between children with similar clinical characteristics 9.…”
Section: Introductionmentioning
confidence: 99%
“…There were 72 events in the RVPA cohort with 68 deaths (25%), four (1 %) heart transplants, and 100 events in the BT shunt group with 91 (33 %) deaths and nine (3 %) heart transplants (p=0.01) . After three years of follow-up, the transplant-free survival was 67% for the RVPA group versus 61 % for the BT shunt group (p=0.15) (Tweddell et al 2012 The SVR trial investigators examined the preoperative mortality and its associated risk factors using all 921 infants with HLHS screened as part of the SVR trial (Atz et al 2010). Major extracardiac congenital abnormality (OR 10.0,p<0.0001), gestational age at birth (OR 1.3, 95% CI 1.1-1.5), p=0.02), and presence of obstructed pulmonary venous return (OR 4.0,p=0.02) were associated with preoperative death pre-Norwood procedure.…”
Section: Mortality In the Single Ventricle Reconstruction Trialmentioning
confidence: 96%
“…Multiple secondary analyses have been published using this dataset. Examples include evaluation of the interstage mortality (Ghanayem et al 2012), risk factors for death or transplant in the intermediate term (Tweddell et al 2012) and 3 years term (Newburger et al 1993), as well as shunt type effect on the cardiac function, ventricular size (Frommelt et al 2012), and ventricular deformation (Hill et al 2015). However, the group of patients with ventricular dysfunction has not been evaluated separately.…”
Section: Reconstruction Trialmentioning
confidence: 99%
“…In the era of personalized medicine, premature and small neonates should not be considered a homogeneous high‐risk category. Although prematurity (<37 weeks’ gestation) and low birth weight (<2.5 kg) increase risk1, 2, 3, 4 on a population basis, the individual preterm or small infant may actually do well. Extrapolating risk from the outcomes of a diverse cohort to an individual is unreliable and potentially misleading, whether it be for counseling a family or discovering novel interventions to improve outcomes.…”
mentioning
confidence: 99%